SIMDARUNG - RANCANG BANGUN SISTEM INFORMASI PENDATAAN WARUNG (Studi Kasus : Dinas Koperasi, UKM dan Perdagangan Kota Administrasi Jakarta Utara) - Dicky Hariyanto; Elvi Sunita Perangin-Angin; Siti Zahrah Zafira (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
In this growing modern era, information systems are very important and major in assisting the business process and improving the performance of an institution. The use of information technology in various aspects of life has evolved and many have changed. The Warung data collection on Suku Dinas Koperasi, Usaha Kecil Dan Menengah Serta Perdagangan Kota Administrasi Jakarta Utara still uses a manual system where the data is still stored in Microsoft Excel on a computer. The most common problem is the possibility of duplication Warung data, theft and editing of data that makes the data security still lacking so that the system updates. On the basis of identification of the problem described above, the problem in this final task is how to make Warung data collection program in the institution to support better performance. Expected data processing stalls can be well integrated, accessible user easily. Designing a system that can provide security so as not to the occurrence of data confusion, data editing and data loss. The system is also expected to generate the official registered Warung data report.